Is less more … or is more less? Scaling the political ecologies of the future. (January 2020) - Robbins, Paul
Abstract: Imagining progressive environmental futures, especially among critical scholars, can be a fraught enterprise. While some theorists and activists turn towards the social emancipatory power of modern technological interventions at scale, others point to the revolutionary power of degrowth, simplicity, and conviviality. These competing political geographical imaginaries are often strident in their response to one another, though they share core materialist commitments. This essay reviews these contrasting approaches in light of the tradition of political ecology, within the context of an Earth economy that is trending towards higher levels of energy and lower levels of human labor, weighing the degree to which the work and conclusions of political ecologists are congruent with either perspective, neither perspective, or both. The conclusions suggest that, while these two traditions have inverse, or at least orthogonal, views of economic scale, they may not be beyond compromise. Socialist modernism and degrowth sprouted from the same seed, share a political ecological tradition, and may indeed require one another. Eschewing both utopian and dystopian aspirations may open the door to progressive reconciliation and action.